Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 29231 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Eucalyptus macta L.A.S.Johnson & K.D.Hill", "TaxonKey is Eucalyptus crebra F.Muell.", "TaxonKey is Eucalyptus mediocris L.A.S.Johnson & K.D.Hill", "TaxonKey is Eucalyptus grandis W.Hill ex Maiden", "TaxonKey is Eucalyptus miniata A.Cunn. ex Schauer", "TaxonKey is Eucalyptus delegatensis F.Muell. ex R.T.Baker", "TaxonKey is Eucalyptus pulchella Desf.", "TaxonKey is Eucalyptus obliqua L'Hér." ] }, "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 29231 records from 52 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006206-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences